Gabon Export Diversification and Competitiveness Report - World Bank (Washington, DC, 2015)
The diagnosis of Gabon's trade potential and the lessons from international experience suggest that, in the long run, the best way to foster export diversification may not be to try to achieve it immediately through providing inefficient incentives but rather to first build domestic capabilities, step by step. To do so, a comprehensive approach that prioritizes and sequences actions needs to be implemented. Key recommendations of this report are to (1) strengthen the regulatory and institutional framework for export promotion, (2) improve the equality of human capital, (3) build a fair and transparent business environment, and (4) upgrade the quality, and reduce the cost, of infrastructure services.